Preliminary piloting and validation of a questionnaire identifying basic clinical skills practised by research nurses. (14th February 2019) - Kirkpatrick, Suriya; Harding, Sam; Pollard, Katherine; Tacchi, Paul
Abstract : Clinical research nurses (CRNs) need to be competent in both clinical and research skills. In the past 10 years there has been increasing focus on developing the research competencies of CRNs. Employers, however, use the nurses' registered status as a proxy measure of clinical competence to perform their duties. The true extent of what clinical skills are practised by CRNs in a large NHS trust is unclear and there is a lack of validated measures to obtain this information. By using a mixed-methods approach of questionnaire and semi-structured interview, we aimed to pilot and validate a questionnaire to identify CRNs' self-reported confidence with clinical skills.